Adaptation and Social Mobility Strategies in Facing Industrialization: Insights from Rural Communities - Syahputra, Maarif; Rianti, Manda (IHSA Institute, 2024)
This research investigates the dynamics of adaptation and social mobility strategies employed by rural communities facing industrialization. Through a mixed-methods approach combining qualitative interviews, focus groups, participant observation, and quantitative surveys, the study examines how rural residents navigate the challenges and opportunities brought about by industrial transformation. The findings reveal a range of adaptation strategies, including economic diversification, promotion of local value chains, social capital formation, and institutional innovation. Moreover, the research highlights the role of education, spatial dynamics, social networks, and human capital in shaping social mobility patterns within rural communities. The implications of the findings for understanding rural development, shaping industrialization policies, and fostering community resilience are discussed, emphasizing the need for holistic, inclusive, and place-based approaches to rural development. Overall, this research contributes to a deeper understanding of the complex interplay between industrialization, adaptation, and social mobility in rural communities, with implications for policy, practice, and future research endeavors.